2014
DOI: 10.1080/13811118.2013.824825
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Models of Suicide

Abstract: Suicidal behavior is highly complex and multifaceted. Consequent to the pioneering work of Durkheim and Freud, theoreticians have attempted to explain the biological, social, and psychological nature of suicide. The present work presents an overview and critical discussion of the most influential theoretical models of the psychological mechanisms underlying the development of suicidal behavior. All have been tested to varying degrees and have important implications for the development of therapeutic and preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 126 publications
(121 reference statements)
1
63
0
1
Order By: Relevance
“…The survey also included assessments of potential confounders based on previous literature on suicide and self-harm (Barzilay and Apter, 2014;Christiansen et al, 2014;Fliege et al, 2009;Haw et al, 2013;Hawton and van Heeringen, 2009;Hawton et al, 2012). These included questions about participant physical health, depressive symptoms, impulsivity, fearfulness, anxiety symptoms, other mental health symptoms, relationship with parents, relationship with friends, sexual orientation, visible minority status, self-esteem, weight image, physical and personality attractiveness (rated by interviewer), parental use of public assistance, intelligence (self-reported and visual IQ test performance), school environment, neighborhood environment, relative physical development, optional thinking, exercise, substance use counseling, psychological counseling, drug and alcohol use, involvement in fights and violence, and exposure to violence.…”
Section: Methodsmentioning
confidence: 99%
“…The survey also included assessments of potential confounders based on previous literature on suicide and self-harm (Barzilay and Apter, 2014;Christiansen et al, 2014;Fliege et al, 2009;Haw et al, 2013;Hawton and van Heeringen, 2009;Hawton et al, 2012). These included questions about participant physical health, depressive symptoms, impulsivity, fearfulness, anxiety symptoms, other mental health symptoms, relationship with parents, relationship with friends, sexual orientation, visible minority status, self-esteem, weight image, physical and personality attractiveness (rated by interviewer), parental use of public assistance, intelligence (self-reported and visual IQ test performance), school environment, neighborhood environment, relative physical development, optional thinking, exercise, substance use counseling, psychological counseling, drug and alcohol use, involvement in fights and violence, and exposure to violence.…”
Section: Methodsmentioning
confidence: 99%
“…Emotional pain Several researchers and theorists suggested that emotional pain is a key component of suicidal behavior (Barzilay & Apter, 2014). Also termed psychological pain, psychache, or mental pain, emotional pain can be defined as intense unpleasant negative emotions which may be characterized by feelings of hurt, anguish, brokenness, and being wounded (Bolger, 1999;Meerwijk & Weiss, 2011;Shneidman, 1999).…”
Section: Social Withdrawalmentioning
confidence: 99%
“…Joiner's interpersonal theory of suicide (IPTS) (Joiner, 2005) is one of a growing number of promising models developed in the last two decades in an attempt to answer empirical questions about the etiology and course of suicidal behavior (Barzilay and Apter, 2014b). The IPTS offers an explanation for suicidal behavior that is testable, consistent with the empirical evidence, and comprehensively addresses the interplay between intra-individual dynamic systems and interindividual risk factors.…”
Section: Introductionmentioning
confidence: 97%